SYSTEMATIC LITERATURE REVIEW: SKEMA BISNIS IT DI ERA SOCIETY 5.0 YANG SESUAI DI INDONESIA - Putra, Candra Adi; Veri, Jhon (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The emergence of the Society 5.0 concept demands the integration of information technology in various aspects of human life, including in business models. This study aims to identify and analyze relevant and appropriate Information Technology (IT) business schemes for implementation in Indonesia within the context of Society 5.0. This study was conducted using the Systematic Literature Review (SLR) method following the PRISMA protocol. Literature was collected from academic databases such as Google Scholar, Scopus, IEEE Xplore, and ScienceDirect, with a total of 156 articles screened until finally 20 articles were selected for qualitative synthesis. The findings indicate that business models based on digital platforms, fintech, agritech, and digital public services are the schemes that best suit Indonesia's digital needs and readiness. In addition, a collaborative, social and community-based approach is also considered effective in empowering the community. This study recommends the development of adaptive, inclusive, and socially impactful IT business models as a key strategy in supporting Indonesia's digital transformation towards Society 5.0.Keywords: Society 5.0, business model, information technology, SLR, Indonesia, digitaltransformation.Abstrak: Munculnya konsep Society 5.0 menuntut integrasi teknologi informasi dalam berbagai aspek kehidupan manusia, termasuk dalam model bisnis. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis skema bisnis Teknologi Informasi (TI) yang relevan dan sesuai untuk diterapkan di Indonesia dalam konteks Society 5.0. Kajian ini dilakukan menggunakan metode Systematic Literature Review (SLR) dengan mengikuti protokol PRISMA. Literatur dikumpulkan dari basis data akademik seperti Google Scholar, Scopus, IEEE Xplore, dan ScienceDirect, dengan total 156 artikel yang disaring hingga akhirnya 20 artikel dipilih untuk sintesis kualitatif. Temuan menunjukkan bahwa model bisnis berbasis platform digital, fintech, agritech, dan layanan publik digital merupakan skema yang paling sesuai dengan kebutuhan dan kesiapan digital Indonesia. Selain itu, pendekatan kolaboratif berbasis sosial dan komunitas juga dianggap efektif dalam memberdayakan masyarakat. Penelitian ini merekomendasikan pengembangan model bisnis TI yang adaptif, inklusif, dan berdampak sosial sebagai strategi utama dalam mendukung transformasi digital Indonesia menuju Society 5.0.Kata Kunci: Society 5.0, model bisnis, teknologi informasi, SLR, Indonesia, transformasi digital.